Hepatocellular Carcinoma in Sub-Saharan Africa. (2021) - Kedar Mukthinuthalapati, V. V. Pavan; Sewram, Vikash; Ndlovu, Ntokozo; Kimani, Stephen; Abdelaziz, Ashraf Omar; Chiao, Elizabeth Yu; Abou-Alfa, Ghassan K.
Abstract : More than 80% of global hepatocellular carcinoma (HCC) patients are estimated to occur in sub-Saharan Africa (SSA) and Eastern Asia. The most common risk factor of HCC in SSA is chronic hepatitis B virus (HBV) infection, with the incidence highest in West Africa. HBV is highly endemic in SSA and is perpetuated by incomplete adherence to birth dose immunization, lack of longitudinal follow-up care, and impaired access to antiviral therapy. HBV may directly cause HCC through somatic genetic alterations or indirectly through altered liver function and liver cirrhosis. Other risk factors of HCC in SSA include aflatoxins and, to a lesser extent, African iron overload. HIV plus HBV co-infection increases the risk of developing HCC and is increasingly becoming more common because of improving the survival of patients with HIV infection. Compared with the rest of the world, patients with HCC in SSA have the lowest survival. This is partly due to the late presentation of HCC with advanced symptomatic disease as a result of underdeveloped surveillance practices. Moreover, access to care and resource limitations further limit outcomes for the patients who receive a diagnosis in SSA. There is a need for multipronged strategies to decrease the incidence of HCC and improve its outcomes in SSA.